Developed Z-Source H-Bridge Multilevel Inverter with Reduced Components for Speed Control of Induction Motor - C. L.Kuppuswamy; T. A. Raghavendiran (Institute of Advanced Engineering and Science, 2018)
This paper introduces a new developed H-bridge based cascaded multilevel inverter with reduced components. This topology has a low complexity thereby reducing the overall cost of an inverter. The proposed circuit is connected with a PI controller and switches are controlled by pulse width modulation technique to control the speed of an induction motor. The simulation was carried out using Matlab / Simulink. The simulation of the same was made and performance of various PWM techniques such as Phase disposition (PD), Phase opposite disposition (POD) and phase shifted (PS) and there results were compared on different quantitative measures such as Voltage, current stator Total harmonic Distortion, Voltage stress and rise time. It was observed that that the proposed power circuit with Phase disposition pulse width modulation (PDPWM) that offers reduced total harmonic Detection in terms of voltage, current and phase was found to be very less when compared to other Pulse width modulation techniques. The simulation results will have a fast and quick rise time thereby making this inverter a choice for speed control of induction motor.